Assessement of Blue Swimming Crab (Portunnus pelagicus) Growth Overfishing at Banten Bay - M J Fauzi; A Gaffar; B Erdyanto; I B Dhewang; M A Arafat; D A Akmalia; Heri Triyono (JURNAL PERIKANAN DAN KELAUTAN, 2018)
This research was conducted in February-March 2018 at Banten Bay. The purpose of research is to determine to presence of growth overfishing of crab (Portunus pelagicus), to cover width-weight relationships, sex ratio, Gonad Maturity Rate (GMR), Length at First Capture (Lc) and Length at first maturity (Lm). The method used is market survey (observation on crab collectors). Temporary research result showed that width-weight relationships are allometrically positive. Sex ratio show a balance value. GMR is the dominant GMR III. Lc 11,26 cm male; 11,38 cm female and Lm 11,82 cm male; 9,30 cm female. Based on the data, it can be seen that the population of the male crabs more quickly decreased compared to the females. If these fishing conditions continue to happen in the long time. It will cause the growth overfishing, result the temporary loss of population and change the food chain.